JUMEK ASKAROVICH URUNOV’S SCIENTIFIC VIEWS ON SCHOOL SYSTEMS - Sultanova Munisa Ulug‘bek qizi (ZAMONAVIY TA'LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2026)
Pedagogical ideas emerged in the early stages of human history. Initially, education was carried out in the family. The elderly taught the younger generation life experiences. In the countries of the ancient East, great attention was paid to science and education. In particular, scholars such as Abu Nasr Al-Farabi, Abu Ali ibn Sina and Alisher Navoi expressed valuable ideas about raising young people to be knowledgeable and polite. For example, Abu Ali ibn Sina emphasized the need to educate children physically, mentally and morally together. Pedagogical ideas play an important role in the development of humanity. The pedagogical views created by Eastern and Western thinkers have made a great contribution to the development of today’s education system. Their ideas have not lost their importance in modern education. A well-rounded generation can be raised through good pedagogical ideas and effective education. Therefore, every teacher must deeply master pedagogical knowledge and modern methods. This can be achieved by purifying behavior and ethics not only in words, but also in reality (in practice). Then it is necessary to cleanse the soul, spirit, and mind of the one who protects from errors and mistakes, who begins to understand the path of truth (in the sense of orator - speaker, thinking).